DAMPAK PENGGUNAAN MEDIA SOSIAL TERHADAP PERILAKU BELAJAR DAN KESEHATAN MENTAL SISWA SD INPRES 1 HALMAHERA UTARA - Hi. Mustafa, Irfandi R; A, Iswadi M; Yamin, Fahrun; Warie, Juliyarti (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
This study aims to determine the impact of social media use on learning behavior and mental health of students at SD Inpres 1 North Halmahera. This study examines how social media affects students' learning behavior and mental health. The research method used in this study is qualitative descriptive research. The data for this study were obtained through observation, interviews, and documentation. The subjects of the study were 40 students at SD Inpres 1 North Halmahera. Meanwhile, the research data collected were analyzed using qualitative descriptive analysis. The results showed that students aged 9 to 12 years, especially grades 4, 5, and 6, had a significant tendency to use social media every day, with grade 6 recording the largest number of users. There is a clear gender difference where female students are more active in using social media than male students. The most frequently used platforms are Facebook, Instagram, WhatsApp, and TikTok. WhatsApp serves as the main tool for communication and academic discussion. Although social media provides several benefits such as access to learning materials, excessive use can interfere with students' learning focus. Many students spend more time socializing on social media than completing academic assignments which has the potential to reduce students' academic achievement. Dependence on social media can also result in difficulty concentrating and negative impacts on mental health, such as stress and anxiety.